Nursing practice of care to patients undergoing elective surgery in the immediate preoperative period - Adnairdes Cabral de Sena; Eliane Regina Pereira do Nascimento; Ana Rosete Maia (2013)
Research that aimed to analyze the care of nurses to patients, in the daily professional practice, provided in the preoperative period for patients undergoing elective surgery. It is a descriptive research with a qualitative approach that involved 15 nurses from Surgical Units and two nurses from the Surgical Centre of a hospital in the southern region of Brazil. Data was collected in semi-structured interviews conducted from April to July 2011. Data was analyzed using the Collective Subject Discourse (CSD) technique. The information obtained generated three CDS focused on the following ideas: administrative care, instruction in the preoperative period and surgical care in the immediate preoperative period. The results showed that caring consists mostly of giving instructions to the patient in the preoperative period. It is concluded that the care was directed to the physical aspects to the detriment of the psychological, in disagreement with the assistance methodology adopted in the hospital, supported by the Theory of Basic Human Needs.